The Impact of Land Use Activities on Vegetation Cover and Water Quality in the Lake Victoria Watershed - Twesigye, Charles K.; Onywere, Simon M.; Getenga, Zachary M.; Mwakalila, Shadrach S.; Nakiranda, Josephine K. (The Open Environmental EngineeringJournal, 2011)
The impact of land use activities on loss of vegetation cover and water quality was assessed in three selected sites within the Lake Victoria Basin using remote sensing technologies and standard water quality analysis techniques. The three study sites were: (i) Nzoia River Basin (Kenya), (ii) Nakivubo Wetland (Uganda) and (iii) Simiyu drainage basin (Tanzania). Lake Victoria is the second largest fresh water lake in the world and is served by a drainage basin area of over 193,000 km2, traversing five East African Community States; Kenya, Uganda, Tanzania, Rwanda and Burundi. This paper examines the impact of land use activities on vegetation cover and water quality based on remote sensing and Geographical Information Systems analysis combined with chemical and physical water analysis. The quality of the effluent generated by the industries found within the study sites and their effects on downstream discharge was also determined. Pesticide residues in soil and water samples were determined using analytical standard methods. Soils from some selected fields in Nzoia River basin showed high levels of compounds such as aldrin, dieldrin, endosulfan, DDT, and endrin which are together referred to as persistent organic pollutants (POPs). The physical and chemical analysis of water quality revealed high levels of phosphates and nitrates along the agricultural zones of River Nzoia Basin. The satellite images revealed that in all the three study sites land vegetation cover has continuously reduced in size. The extent of environmental degradation caused by agricultural, domestic and industrial wastes and how this affects loss of vegeta-tion cover and water quality is discussed.
Keywords: GIS analysis; Lake Victoria,; Land use; remote sensing; vegetation cover; water quality; watershed